Navigating the Clinical Landscape of Liposomal Therapeutics in Cancer Treatment - Andreja Kozak; Ernestina Lavrih; Georgy Mikhaylov; Boris Turk; Olga Vasiljeva (Pharmaceutics)
Liposome-based targeted drug delivery systems represent a significant advancement in pharmaceutical science, offering distinct advantages that enhance the efficacy and safety of various therapies. These versatile carriers can encapsulate both hydrophilic and hydrophobic drugs, making them particularly valuable in clinical settings. This review explores the critical role of liposomal formulations in improving drug pharmacokinetics and minimizing side effects, especially in oncology, where targeted delivery to tumor cells is essential. Outlining the properties of different types of liposomes, we focus on the effects of these properties on the liposomes’ targeting and drug release capabilities through innovative surface modifications and describe the most common methods of liposome preparation and characterization. Furthermore, this review provides an in-depth analysis of the properties and composition of liposomal-based nanocarriers, with a unique focus on ongoing clinical trials and recently approved therapies. It offers a comprehensive overview of the latest advancements in pre-clinical research and highlights the critical progress in clinical development, offering insights into the clinical impact and regulatory approvals. Ultimately, this review underscores the transformative potential of liposomal nanocarriers in modern therapeutics, suggesting avenues for future innovations and clinical breakthroughs.